Under the sword of Damocles: Exploring the well-being of university academics during a crisis - Subban, Pearl; Laletas, Stella; Creely, Edwin; Southcott, Jane; Fernandes, Venesser (Frontiers in Education, 2022)
Prompted by the wide-spread impact of the global pandemic on the higher education sector in Australia, this study explores the wellbeing and mental health of university academics. The mixed-methods study has three objectives: the design and development of an instrument; administration of the survey, constructed in the form of a matrix, to a randomly drawn sample of academic university staff; via a set of open-ended questions, exploration of strategies listed by participants. An initial validation study, the project encapsulated scale design, generating a tool which measures the wellbeing of university academics, especially during times of crisis. The measurement tool was constructed in four parts utilising the established formula of academic workload, Teaching, Research, Service/Engagement, and Demographic variables. Findings suggested that most academics were concerned about the maintenance of their research output and teaching workloads. Maintaining responsibilities as care-givers and parents of school-going children proved challenging. Many conceded that maintaining equilibrium was complex. It is anticipated that the scale will be an effective means of quantifying academic wellbeing, thereby offering a valid instrument to university leaders, when considering staff wellbeing in the contemporary context.